The EQ-5D-5L index as a measure of health-related quality of life in type 2 diabetes: a systematic review and meta-analysis - Adrianapia Maria Lamedica; Elena Tortato; Federica Turchi; Maria Paola Luconi; Luca Antognoli; Angelica Giuliani; Fabiola Olivieri; Liana Spazzafumo; Anna Rita Bonfigli (Frontiers in Endocrinology, 2026)
Introduction Type 2 diabetes (T2D) substantially impairs health-related quality of life (HRQoL). Although the EQ-5D-5L index is a validated instrument for measuring health utilities in this patient population, it remains underutilized in clinical practice. This review synthesizes current evidence regarding its cross-sectional sensitivity to the clinical burden of T2D. Methods Following PRISMA 2020 guidelines, PubMed, Embase, Scopus, Web of Science, and ScienceDirect were searched for cross-sectional studies published from January 2000 to September 2025 reporting EQ-5D-5L index values in community-dwelling adults with T2D. Results Forty-two studies were included, encompassing 32, 782 patients with T2D. The evidence shows significant sample size heterogeneity (ranging from 93 to 13, 966 subjects) and a stark geographic imbalance, with 69.05% of studies conducted in Asia. Results indicate that while uncomplicated T2D has a limited impact on HRQoL, the accumulation of comorbidities drastically reduces patient well-being. Specifically, cross-sectional data show a consistent inverse correlation between clinical burden and EQ-5D-5L index scores; the lowest utility values were observed in patients with diabetic complications and comorbidities, as well as those characterized by adverse socio-demographic factors, including advanced age, low education, and poverty. The substantial heterogeneity observed across the included studies was further confirmed and quantified by the meta-analysis. Conclusion While the EQ-5D-5L index is a reliable tool for cross-sectional HRQoL assessment in T2D, longitudinal studies are needed to determine if declining index values prospectively predict diabetes complications. Ultimately, routine clinical integration of the EQ-5D-5L holds promise for personalizing care and optimizing long-term quality of life in aging patients. Systematic review registration OSF, identifier DOI 10.17605/OSF.IO/BQYR7.